Mechanisms and therapeutic implications of gene expression regulation by circRNA-protein interactions in cancer - Nan Zhang; Xinjia Wang; Yu Li; Yiwei Lu; Chengcheng Sheng; Yumeng Sun; Ningye Ma; Yisheng Jiao (Communications Biology)
Abstract Circular RNAs (circRNAs) have garnered substantial attention due to their distinctive circular structure and gene regulatory functions, establishing them as a significant class of functional non-coding RNAs in eukaryotes. Studies have demonstrated that circRNAs can interact with RNA-binding proteins (RBPs), which play crucial roles in tumorigenesis, metastasis, and drug response in cancer by influencing gene expression and altering the processes of tumor initiation and progression. This review aims to summarize the recent advances in research on circRNA-protein interactions (CPIs) and discuss the functions and mode of action of CPIs at various stages of gene expression, including transcription, splicing, translation, and post-translational modifications in the context of cancer. Additionally, we explore the role of CPIs in tumor drug resistance to gain a deeper understanding of their potential applications in the development of new anti-cancer therapeutic approaches.